Perspectives on the adoption of black-soldier fly larvae for animal feed among livestock farmers in Sub-Saharan Africa. - Nyamuhirwa, D.A.; Feleke, S.; Dontsop Nguezet, P.; Sissoko, D.; Moussa, B.; Kouakou, A.; Zakari, S.; Abdoulaye, T.; Manyong, V. (2025)
Introduction: Black soldier fly larvae (BSFL) are increasingly promoted as cost-effective, and environmentally friendly source of protein in animal nutrition. However, there is limited information about farmers' adoption rates and the factors influencing their adoption decisions in Sub-Saharan Africa (SSA). This article assesses livestock farmers' actual and potential adoption rates of BSFL and determinants of their adoption decisions.